Oxidation of polychlorinated benzenes by genetically engineered CYP101 (cytochrome P450(cam)). - Jones, J; O'Hare, E; Wong, L (2001)
Polychlorinated benzenes are recalcitrant environmental pollutants primarily because they are resistant to attack by dioxygenases commonly used by micro-organisms for the biodegradation of aromatic compounds. We have investigated the oxidation of polychlorinated benzenes by mutants of the haem mono-oxygenase CYP101 (cytochrome P450(cam)) from Pseudomonas putida with the aim of generating novel systems for their biodegradation. Wild-type CYP101 had low activity for the oxidation of dichlorobenzenes and trichlorobenzenes to the chlorophenols, but no products were detected for the heavily chlorinated benzenes. Increasing the active-site hydrophobicity with the Y96F mutation increased the activity up to 100-fold, and both pentachlorobenzene and hexachlorobenzene were oxidized slowly to pentachlorophenol. Decreasing the space available at the top of the active site with the F87W mutation to force the substrate to be bound closer to the haem resulted in a further 10-fold increase in activity with most substrates. Introducing the F98W mutation, also at the top of the active site, decreased the NADH-turnover rates but increased the coupling efficiencies, and > 90% coupling was observed for 1,3-dichlorobenzene and 1,3,5-trichlorobenzene with the F87W--Y96F--F98W mutant. The V247L mutation generally increased the NADH-turnover rates, and the F87W--Y96F--V247L mutant showed reasonably fast NADH turnover (229 min(-1)) with the highly insoluble pentachlorobenzene without the need for surfactants or organic cosolvents. As all chlorophenols are degraded by micro-organisms, novel biodegradation systems could be constructed in which CYP101 mutants convert the inert polychlorinated benzenes to the phenols, which are then readily degraded by natural pathways.